Draft genome and description of Mixta mediterraneensis strain Marseille-Q2057T sp.nov., a new bacterium isolated from human healthy skin. (March 2021) - Boxberger, M.; Antezack, A.; Magnien, S.; Cassir, N.; La Scola, B.
Abstract: In 2019, by culturing a skin swab from the hand of a 30-year-old healthy woman using the culturomic method, we isolated the new bacterial strain Marseille-Q2057 T (= CSUR-Q2057). Matrix-assisted desorption–ionization time-of-flight mass spectrometry (MALDI-TOF MS) failed to identify this isolate. Analysis of the 16S rRNA gene and Genome-to-Genome comparison suggested that this taxon belongs to a novel bacterial species within the family Erwiniaceae, phylum Proteobacteria. We describe here its main phenotypic characteristics, genome sequence and annotation of Mixta mediterraneensis strain Marseille-Q2057 T, a new member of the Mixta genus, that we propose as type strain.